Geoheritage and Geotourism Resources Education, Recreation, Sustainability - Drinia, Hara; Voudouris, Panagiotis; Antonarakou, Assimina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue reprint entitled "Geoheritage and Geotourism Resources: Education, Recreation, Sustainability", aims to highlight, review and evaluate the usefulness of geo-cultural features in didactics in terms of geoparks and other geotouristic attractions. Innovative methods of geo-education in geoparks are presented, as well as the development of research combining the geosciences with the social science and humanities. The essential role of geoheritage in the popularization of knowledge is emphasized.